Incidence of giardiasis in the Karaganda region (Eurasian Journal of Ecology, 2016)
Objective: The aim of investigation was to evaluate territorial incidence of giardiasis in the Karaganda region for 2010-2011y. We conducted retrospective statistical population study by a selective method on theout-patient clinics in Karaganda and the cities satellites. 12547 patients were included in research with suspicion on giardiasis. According to the results of our study the incidence rate of giardiasis in the Karaganda region was 4.4 per 1,000 people as of stool microscopy, 8.7 per 1,000 people by the result of ELISA .The coincidence percent between these methods made 11% and respectively incidence on two methods was 2,0 on 1000 people.
Keywords: giardiasis; incidence of giardiasis; identification of specific antibodies in serum by ELISA; threenative microscopy samples of faeces